Vehicle-to-anything: a power transfer perspective for vehicle electrification - Monteiro, Vítor Duarte Fernandes (2019)
The concept of vehicle-to-anything (V2X) is mainly focused on the bidirectional communication between any technology of vehicle and any external system that can contribute for its operation. However, prospecting the vehicle electrification, this concept can also be associated with the power transfer between an electric vehicle (EV) and any external system, where bidirectional communication is absolutely fundamental. Within the power transfer, the possibility of exchanging active power between an EV and the power grid is considered as a promising operation mode, especially considering the possibility of selling demand response services for the electrical power grid. Contemplating the vehicle electrification context, in addition to the latent possibility of interaction between EVs and the power grid for active power exchange, other possibilities of interaction can also be considered, providing advantageous services for the power grid. Thus, this article approaches the V2X concept for off-board systems in the power transfer perspective for vehicle electrification, aggregating new contributions related with the interaction between an EV and any external electrical system (operating as source or load), and both from on-grid or off-grid point of view. Contributions are meticulously presented, recognizing their advantages and disadvantages in a real-scenario of operation. A comparison in terms of cost of implementation and in terms of efficiency is presented considering the various solutions of the vehicle electrification in a smart grid perspective.